Pelatihan Pengukuran Antropometri Balita Pada Kader Posyandu di Desa Lombuea Kecamatan Moramo Utara Kabupaten Konawe Selatan - Paridah; Yusran, Sartiah; Bahar, Hartati; Lestari, Hariati; Annaba, Muh. Fitra; Yani, Indra; Zahrah, Inayah (Jurnal Pengabdian Masyarakat (JUDIMAS), 2025)
The Healthy Indonesia Program aims to improve the health and nutritional status of the community through health efforts and community empowerment supported by financial protection and equitable distribution of health services. One of the 12 indicators of the Healthy Indonesia Family Approach Program is the growth of toddlers which is monitored every month. Posyandu cadres are the central point for conducting initial screening for nutritional problems through monitoring the nutritional status of toddlers at Posyandu. The aim of this activity is to evaluate and refresh methods for measuring toddler anthropometry at Posyandu Cadres in Lombuea Village, North Moramo District. This activity began with a pre-test on the skills of Posyandu cadres in carrying out anthropometric measurements, then a simulation of how to measure anthropometrically well and correctly was given by the Healthy Village Team. The pre-test results show that it is true that Posyandu cadres still have errors during anthropometric measurements which can influence the measurement results. After being given a simulation on how to measure anthropometrically for babies and toddlers properly and correctly, Posyandu cadres are aware of several errors during measurements and know how to measure well. and true. It is recommended that cadres continue to refresh anthropometric measurements of toddlers so that they can carry out measurements accurately so that assessing the nutritional status of toddlers at posyandu can also produce data that is appropriate to the condition of babies and toddlers